Role of phosphoenolpyruvate carboxylase in the adaptation of a tropical forage grass to low-phosphorus acid soils - Begum, Hasna Hena; Osaki, Mitsuru; Nanamori, Masahito; Watanabe, Toshihiro; Shinano, Takuro; Rao, Idupulapati M. (Informa UK Limited, 2006)
As Brachiaria hybrid cv. ‘Mulato’ has adapted to acid soils with extremely low phosphorus (P) contents, its low-P-tolerance mechanisms were investigated and compared with those of wheat (Triticum aestivum L.) and rice (Oryza sativa L. cv. ‘Kitaake’). Among the three plant species, the highest P-use efficiency (PUE) in low-P soil was recorded in the Brachiaria hybrid, which increased remarkably under P-deficiency and soil acidity, while P-deficiency had less effect on the PUE of wheat and rice. As exudation of organic acid anions from roots is considered to be one of the most important mechanisms of adaptation to low-P soil, the role of phosphoenolpyruvate carboxylase (PEPC), which is closely related to organic acid metabolism and Pi recycling in C3 plants, was studied. As expected, the PEPC activity of the Brachiaria hybrid (C4 plant) leaves was 51- to 129-fold higher than that estimated for wheat and rice (both C3 plants). PEPC activity in leaves and roots of the Brachiaria hybrid increased up to two-and three-fold, respectively, and decreased the malate-inhibition ratio in leaves in response to P-deficiency. However, PEPC activity and malate-inhibition ratio were less affected in wheat and rice under P-deficiency. The Brachiaria hybrid synthesized higher amounts of organic acids (e.g., oxalate and fumarate) in leaves, especially under P-deficiency. Results from these experiments indicate that PEPC activated in the Brachiaria hybrid under low-P and low-pH conditions may contribute to the plant's greater adaptation to tropical acid soils with P-low availability.